1996
DOI: 10.1007/bf02628669
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on the use of transfer factor for treating stage D3 hormone-unresponsive metastatic prostate cancer

Abstract: As conventional treatments are unsuccessful, the survival rate of stage D3 prostate cancer patients is poor. Reports have suggested the existence of humoral and cell-mediated immunity (CMI) against prostate cancer tumour-associated antigens (TAA). These observations prompted us to treat stage D3 prostate cancer patients with an in vitro produced transfer factor (TF) able to transfer, in vitro and in vivo, CMI against bladder and prostate TAA. Fifty patients entered this study and received one intramuscular inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
13
1
1
Order By: Relevance
“…15 However, in new trials, TF may not be easy to use since its production is not standardized and its effects have been challenged. Indeed, TF is considered by many to be too unreliable for treatment, despite hundreds of reports proving its efficacy in treating not only cancer but also viral, fungal and parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, in new trials, TF may not be easy to use since its production is not standardized and its effects have been challenged. Indeed, TF is considered by many to be too unreliable for treatment, despite hundreds of reports proving its efficacy in treating not only cancer but also viral, fungal and parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…TF injections. In our institution, TF is currently used as an adjuvant treatment of certain tumors, i.e., non-small-cell lung cancer 14a and hormoneunresponsive prostate cancer, 15 with promising clinical results.…”
mentioning
confidence: 99%
“…Dialyzable Leukocyte Extract (DLE) has been used for the treatment of many inflammatory diseases, like osteoarthritis [8], autoimmune [9], bacterial [10], and viral [11] diseases among others. Pizza et al in 1996 showed that DLE promoted cancer remissions and increased the survival of prostatic cancer patients [12]. Here, we report using a modified Experimental Autoimmune Prostatitis model [13], the effects of DLE treatment in autoimmune prostatitis through histopathological analysis, the detection of prostatein by Enzyme-Linked Immunosorbent Assay (ELISA), and immunohistochemical staining for anti- and proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 93%
“…Pizza et al [45] conducted a follow-up investigation, ranging from 1 to 9 years. They were treated with TF 50 patients with prostate cancer unresponsive to conventional therapy.…”
Section: Cancermentioning
confidence: 99%